Does AI Make Healthcare More Affordable for Me? A Professional and Academic Perspective - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Introduction: The Promise and the Price Tag of AI in Healthcare The integration of Artificial Intelligence (AI) into healthcare is a transformative shif...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation